The Students’ Well-Being in Online Speaking Class During Pandemic (A Quasi-Experimental Study in Academic Speaking Class) - Farid Noor Romadlon; Mochlis Ekowijayanto (International Journal of English Education and Linguistics (IJoEEL), 2022)
Student welfare has an important function. Pandemic completely affects the world, especially teaching and learning activities. This study focuses on the impact of student prosperity on student academic performance in the learning process Speaking in online class during pandemic, find out students’ academic performance enhancement after conducting online speaking class using Zoom platform, and know students’ responses in the use of Zoom platform in online speaking class. This course uses One Group Pretest-Posttest Design through which 32 students in the fourth semester of the English Education Department are reviewers. The instruments used to research are student prosperity questionnaires, student pretest-posttest papers, and student response questionnaires. Obtaining a student t prosperity questionnaire before and after the use of Zoom platform tested correlation brings up numbers 0.038 and coefficient of relationship 0.41. The students' pretest and posttest scores were tested through the paired sample T-test, which was significant 6% giving a score of 0.003. The student's idea acquisition is ≥ 630% in accordance with the provisions. So it can be concluded that students’ well-being is well-maintained in speaking online class during a pandemic using the Zoom platform.